Palatal mucosa thickness and palatal neurovascular bundle position evaluation by cone-beam computed tomography—retrospective study on relationships with palatal vault anatomy - Karadag,Ilkim; Yilmaz,Hasan Guney (PeerJ, 2021)
Background Measuring the thickness of the palatal mucosa at the planning of the surgical procedure is an important step in order to obtain the maximum width and thickness of the graft from the appropriate area. The aim of this study is to determine whether there is a relationship between palatal angle (PA) or palatal depth (PD) and palatal mucosa thickness (PMT) or palatal neurovascular bundle distance (PNBD). Methods PMT, PNBD, PD and PA were measured on cone-beam computed tomography (CBCT) images of maxillary posterior region of 200 male and 200 female patients. The mean of all parameters according to gender was compared and the significance of the difference detected between groups was evaluated. Potential relationship between PMT or PNBD and PA or PD was also evaluated. Results In females, the palatal mucosa was significantly thinner at all tooth regions (p < 0.005), and PNBD was lower only at the level of the second molar (p < 0.001). In addition, it was found that there was a significant inverse correlation between the palatal depth value and the palatal mucosal thickness, and palatal depth was correlated with the palatal neurovascular bundle distance (p ≤ 0.001). Discussion Consistent with previous studies, it was observed that the thickest mucosa in the palatal region was located in the region of the premolar teeth, and women had thinner palatal mucosa. In addition, in patients with a deeper palate vault, the palatal mucosa was thinner, but the palatal neurovascular bundle was more distant from the cemento-enamel junction.
Keywords: Palatal mucosa; Palatal neurovascular bundle; Subepithelial connective tissue graft; CBCT